RETRACTED : KEPEMIMPINAN DAN INTEGRITAS TERHADAP KINERJA ORGANISASI DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING - Ali, Maulana (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2019)
Following a rigorous, carefully concerns and considered review of the article published in jurnal Nusantara Aplikasi Manajemen Bisnis to article entitled “Kepemimpinan dan Integritas Terhadap Kinerja Organisasi dengan Komitmen Organisasi sebagai Variabel Intervening ” Vol 4, No 1, pp. 28 - 37, April 2019, DOI: https://doi.org/10.29407/nusamba.v4i1.12700 The article contained redundant material, the editor investigated and found that the paper is same with thesis Bonny Rakhmanto at Universitas Mercu Buana 2018 The document and its content has been removed from jurnal Nusantara Aplikasi Manajemen Bisnis and reasonable effort should be made to remove all references to this article.